2014
DOI: 10.1186/s12932-014-0012-y
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur and oxygen isotope insights into sulfur cycling in shallow-sea hydrothermal vents, Milos, Greece

Abstract: Shallow-sea (5 m depth) hydrothermal venting off Milos Island provides an ideal opportunity to target transitions between igneous abiogenic sulfide inputs and biogenic sulfide production during microbial sulfate reduction. Seafloor vent features include large (>1 m2) white patches containing hydrothermal minerals (elemental sulfur and orange/yellow patches of arsenic-sulfides) and cells of sulfur oxidizing and reducing microorganisms. Sulfide-sensitive film deployed in the vent and non-vent sediments captured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 105 publications
(172 reference statements)
2
38
0
Order By: Relevance
“…Heat deep within the smokers keeps metal sulfides in solution, and acidity favors their dissociation and elevates H 2 S concentrations (51). In the prebiotic earth, it is quite likely that H 2 S and reduced metal sulfides remained in solution in anoxic seawater for prolonged periods and could have spread considerable distances (35). Present-day vents contain the densest biomass on earth, evidence of their abundant energy and the ability of living organisms to use that energy.…”
Section: Origin Of Lifementioning
confidence: 99%
“…Heat deep within the smokers keeps metal sulfides in solution, and acidity favors their dissociation and elevates H 2 S concentrations (51). In the prebiotic earth, it is quite likely that H 2 S and reduced metal sulfides remained in solution in anoxic seawater for prolonged periods and could have spread considerable distances (35). Present-day vents contain the densest biomass on earth, evidence of their abundant energy and the ability of living organisms to use that energy.…”
Section: Origin Of Lifementioning
confidence: 99%
“…A number of studies have identified and successfully characterized microbial communities thriving in hydrothermal vent fields impacted by some of the most elevated As concentrations (e.g., Dando et al 1995; Bayraktarov et al 2013; Giovannelli et al 2013; Price et al 2013a, b; Ruiz-Chancho et al 2013; Gilhooly et al 2014; Godelitsas et al 2015; Callac et al 2017). Nonetheless, a mechanistic understanding of how life copes with high As conditions, the chemical and physical processes that regulate dissolved As content, and the potentially biolimiting phosphate concentrations caused by coprecipitation with hydrothermal Fe(III)(oxyhydr)oxides (e.g., Feely et al 1996, 1998; Wheat et al 1996; Schaller et al 2000; Hawkes et al 2014), remain to be clarified for these environments.…”
Section: Introductionmentioning
confidence: 99%
“…For example, at Vulcano Island (Italy) mixed fluids (~40-90°C) have been described with pH as low as ~2, sulfate levels up to ~60 mM, and sulfide up to ~0.4 mM (28,29). At Milos Island (Greece) fluids are lower in sulfate (up to ~33 mM), but more sulfidic (up to 3 mM) (30,31 Caption for Figure 1. Values of ∆ !…”
Section: Resultsmentioning
confidence: 99%